1989
DOI: 10.1029/jd094id04p05189
|View full text |Cite
|
Sign up to set email alerts
|

Continuing current in negative cloud‐to‐ground lightning

Abstract: Simultaneous single‐station electric field and multiple‐station TV measurements on 90 negative cloud‐to‐ground lightning flashes that occurred on 3 days in July 1979 near Tampa, Florida, have been analyzed for the following characteristics of electric field changes indicative of continuing current: frequency of occurrence, duration, duration of interstroke interval preceding, duration of interstroke interval containing, current and charge transferred, and magnitude of initiating return‐stroke electric field pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 10 publications
8
68
2
Order By: Relevance
“…Similar results were found in other studies [41]. It is reported that fires occurring on terrain facing suntraps were more likely to spread due to higher solar incidence and comparatively drier fuel [42].…”
Section: Environmental Determinants Of Lightning Fire Occurrencesupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were found in other studies [41]. It is reported that fires occurring on terrain facing suntraps were more likely to spread due to higher solar incidence and comparatively drier fuel [42].…”
Section: Environmental Determinants Of Lightning Fire Occurrencesupporting
confidence: 80%
“…Lightning is more likely to cause ignition due to a greater likelihood of a long continuum current [30,31,40]. Shindo and Uman [41] studied 90 cloud-to-ground discharges and found that only 1 of 19 single-stroke discharges was followed by a long-continuing current, whereas 21 discharges of the remaining 71 multiple-stroke discharges contained a long continuum current. These results supported our findings that increased probability of multiple-stroke discharges leaded to an increased probability of ignition.…”
Section: Environmental Determinants Of Lightning Fire Occurrencementioning
confidence: 99%
“…Our collection methodology does not allow us to estimate continuing currents directly, but some estimates can be made. As observed by [24], high multiplicity means a high probability of a continuing current. Similarly, high positive currents tend to imply continuing currents [8].…”
mentioning
confidence: 91%
“…Shindo and Uman [1989] once grouped the continuing current into three categories according to their duration: long continuing current with duration exceeding 40 ms, short continuing current with duration between 10 ms and 40 ms, and questionable continuing current with duration between 1 ms and 10 ms. For easy comparison, the same definition is followed in the following statistical analysis. Of all the 185 positive flashes, 133 (71.89%) contained continuing current with duration longer than 1 ms, including 36 long, 47 short, and 50 questionable continuing currents.…”
Section: Duration Of Continuing Currentmentioning
confidence: 99%